Ablenkung im Straßenverkehr und deren Einfluss auf das Fahrverhalten - Kettwich, Carmen (Spektrum der Lichttechnik / Karlsruher Institut für Technologie (KIT), Lichttechnisches Institut, 2014)
Nowadays drivers have to get along with an increasing complex visual environment in road traffic. There are not only distractions available within the vehicle, like radio, navigation system and passengers. The environment outside the car becomes also more and more complex. Car drivers’ gaze behaviour while being distracted is studied on the basis of some examples. Furthermore different performance indicators are analysed.